Temporal and spatial dynamics of urban heat in the City of Córdoba, Argentina - Sangermano, Florencia (2025)
Introduction: Climate change is expected to exacerbate the Urban Heat Island (UHI) effect in the coming decades by altering the structure and function of urban ecosystems and impacting human health. Methods: This research assesses the dynamics of the UHI effect in the city of C´ ordoba, Argentina, by analyzing temperature trends over the past 19 years. Urban areas were classified into five classes using satellite imagery. Monthly average daytime and nighttime MODIS Land Surface Temperature (LST) were used to assess thermal differences across urban classes and temporal trends. Results: Daytime urban cooling occurred during the winter and heating during the summer, while at nighttime, the city experienced heating year-round. Over 19 years, urban areas presented the highest significant increase in temperature during nighttime, with some areas also experiencing increases during both day and night. Shrub lands and crops also showed an increase in LST, particularly during nighttime. Increasing trends in LST during the night overlap with 89.2 % of the population, 90.5 % of households, and 87 % of households with unsatisfied basic needs. Discussion: The population of the city of C´ordoba is highly exposed to the UHI, and the exposure is intensifying, potentially leading to heat-related diseases, spreading disease vectors such as mosquitoes, increasing energy and water consumption, and decreasing the overall quality of life for city dwellers.